1997
DOI: 10.1021/la970347o
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Viscoelasticity of Sodium 1-Oxo-1-[4-(tridecafluorohexyl)phenyl]-2-hexanesulfonate Aqueous Solutions

Abstract: The thermal viscosity behavior or temperature-dependent viscosity of an aqueous solution of sodium 1-oxo-1-[4-(tridecafluorohexyl)phenyl]-2-hexanesulfonate (FC6-HC4), a fluoro-hybrid type surfactant, which has a fluorocarbon chain and a hydrocarbon chain in a molecule, was examined. The FC6-HC4 solution showed viscoelastic behavior at concentrations around 10 wt %. Further study on the temperature dependence of the viscosity of a 10 wt % solution revealed that the viscosity increased about 102 times, showing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 57%
“…We have reported a peculiar viscosity behavior of highly concentrated aqueous solutions of the hybrid surfactants (8)(9)(10)(11)(12). Figure 6 shows typical photographs of 1, 5, 10, and 20 wt% solutions of F8EH3OS at 25 .…”
Section: Solution Properties Of Fmehnos At High Concentrationsmentioning
confidence: 99%
“…; however, reports on heat-induced gels formed from low-molecular weight compounds remain limited. Tobita et al 8 showed that the viscosity of a fl uorohybrid-type surfactant solution increased gradually over a wide temperature range of 10-36 , with a maximum viscosity at 36 , which decreased upon further heating. Similar viscosity curves upon heating have also been observed in other surfactant solutions 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Tobita et al 8 showed that the viscosity of a fl uorohybrid-type surfactant solution increased gradually over a wide temperature range of 10-36 , with a maximum viscosity at 36 , which decreased upon further heating. Similar viscosity curves upon heating have also been observed in other surfactant solutions 8,9 . In the heat-induced gelation of surfactants, the phase transitions generally occur over a broad temperature range and the surfactant pounds apart from LiCl would be effective in forming O/W emulsions of C18AA to act as heat-induced gels.…”
Section: Introductionmentioning
confidence: 99%
“…Although almost no surface activity data were obtained with the hybrid surfactants with long fluorocarbon and hydrocarbon chains because of their insolubility in water, F6H5OS and F8H3OS had Krafft points of 14 and 16 , respectively, which are comparable with that of sodium lauryl sulfate, a typical anionic hydrocarbon surfactant, and showed an excellent surface tension lowering ability. In addition, their concentrated solutions exhibited a high viscosity caused by changes in concentration and temperature as those of the sulfonate-type hybrid anionic surfactants did (5)(6)(7). We then investigated the properties of dilute solutions of these two hybrid surfactants in more detail in the present work.…”
mentioning
confidence: 96%